Transcending diversity - Anne Leonard; Ursula Stroh (Communicare)
Although the philosophy of ethical and socially responsible communication management' practices has a long history and has been described in great detail, the notion of the communication manager as an ethical/moral ombudsperson is relatively new. With increasing numbers of communication managers now forming part of the dominant coalition/strategic decision-making team in many organisations, the real influence that these individuals have over the values that organisations accept should be critically assessed. The new role of the communication manager is conceptualised as constituting two spheres of responsibility. Internally the communication manager should be facilitating the establishment and acceptance of ethically/morally acceptable organisational values. These values will then figure in external organisational behaviour, while the communication manager will act as the eyes and ears of the society in which he/she operates.